2019
DOI: 10.3389/fpsyg.2019.01327
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization-Based Treatment From the Patients’ Perspective – What Ingredients Do They Emphasize?

Abstract: Objective: The aim of this study was to explore how patients with personality disorder (PD) and substance use disorder (SUD) experience mentalization-based treatment (MBT), in particular what they consider useful and less useful elements of the therapy. Method: Semi-structured qualitative interviews with 13 participants were conducted. Participants were interviewed on their experience of the different elements of MBT, their experience of working in the transference, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
1
24
0
1
Order By: Relevance
“…Our findings on normalization also support Morken et al (2019b), who explored how patients with BPD features and substance use experienced mentalization-based treatment, and Farrell et al (2009), who published the first randomized controlled trial on schema therapy groups. Morken et al (2019b) found that by identifying with others with similar problems, patients who had suffered from shame and a sense of being bad achieved a sense of self-worth. After listening to co-patients, they felt normalized and less alone and bad.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings on normalization also support Morken et al (2019b), who explored how patients with BPD features and substance use experienced mentalization-based treatment, and Farrell et al (2009), who published the first randomized controlled trial on schema therapy groups. Morken et al (2019b) found that by identifying with others with similar problems, patients who had suffered from shame and a sense of being bad achieved a sense of self-worth. After listening to co-patients, they felt normalized and less alone and bad.…”
Section: Discussionsupporting
confidence: 81%
“…As a capacity, it is similar to reflective function in mentalization theory (Bateman and Fonagy, 2016). Indeed, patients with personality disorders and low capacity for mentalization have expressed their wish for therapists who communicate clearly in the therapeutic setting (Morken et al, 2019), indicating that patients in the present study would have benefitted from such an approach as opposed to the restrained version of the psychoanalytic stance they described their therapists applied. When not noticing the sudden shifts in mentalization capacity, the therapist underestimates the patient's difficulties which leads to interventions not adjusted to patient's level and needs.…”
Section: Secondary Analysis: Preventing Suboptimal Psychotherapy With Young Adultsmentioning
confidence: 72%
“…Several qualitative studies describing change processes among BPD patients have indeed highlighted the subjective impact of new relational experience, practice, and competence ( 47 50 ). Positive patient-reported group experiences—learning to gain and lend perspectives are indeed emphasized in a qualitative study of MBT ( 51 ). In our study, patient’s self-report indicated improvement of interpersonal problems among patients with mainly hypermentalizing problems.…”
Section: Discussionmentioning
confidence: 99%